2012
DOI: 10.3390/nu4070676
|View full text |Cite
|
Sign up to set email alerts
|

Zinc and Regulation of Inflammatory Cytokines: Implications for Cardiometabolic Disease

Abstract: In atherosclerosis and diabetes mellitus, the concomitant presence of low-grade systemic inflammation and mild zinc deficiency highlights a role for zinc nutrition in the management of chronic disease. This review aims to evaluate the literature that reports on the interactions of zinc and cytokines. In humans, inflammatory cytokines have been shown both to up- and down-regulate the expression of specific cellular zinc transporters in response to an increased demand for zinc in inflammatory conditions. The acu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
172
1
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 242 publications
(186 citation statements)
references
References 100 publications
(128 reference statements)
6
172
1
7
Order By: Relevance
“…5 One major monocyte function is cytokine production, and zinc influences the release of inflammatory cytokines, even though the results so far have been highly contradictory. 6 Lipopolysaccharide (LPS), part of the cell wall of gramnegative bacteria, is one of a myriad of agents that leads to secretion of monokines such as tumor necrosis factor (TNF)-a and interleukin (IL)-6. Their release in response to stimulation using LPS can be enhanced in peripheral mononuclear blood cells (PBMC) by zinc supplementation, 4,7 and intracellular zinc signals are required for the production of pro-inflammatory cytokines in response to LPS.…”
Section: Introductionmentioning
confidence: 99%
“…5 One major monocyte function is cytokine production, and zinc influences the release of inflammatory cytokines, even though the results so far have been highly contradictory. 6 Lipopolysaccharide (LPS), part of the cell wall of gramnegative bacteria, is one of a myriad of agents that leads to secretion of monokines such as tumor necrosis factor (TNF)-a and interleukin (IL)-6. Their release in response to stimulation using LPS can be enhanced in peripheral mononuclear blood cells (PBMC) by zinc supplementation, 4,7 and intracellular zinc signals are required for the production of pro-inflammatory cytokines in response to LPS.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro studies using different cell types and zinc concentrations as well as the impact of chelating agents have made it obvious that the influence of zinc cannot be interpreted using a unilateral approach [35]. For instance, a study by Haase et al have revealed that zinc is necessary for the activation of lipopolysaccharide (LPS)-induced NF-κB signalling pathway, whereas chelating zinc with membrane permeable zinc specific chelator TPEN (N,N,N',N'-tetrakis-(2-pyridyl-methyl) ethylenediamine) completely blocked this pathway [36].On the other hand, there is a growing body of literature that supports the role of zinc as a negative regulator of NF-κB signalling pathways.…”
Section: A Nf-κb and Other Signalling Pathwaymentioning
confidence: 99%
“…Важную роль в развитии данного воспалительного компонента, вероят-но, играет ядерный фактор транскрипции -NF-κB. Этот фактор вовлечен в процессы синтеза провоспалительных цитокинов и его активация, действительно, происходит в легких при повреждении, инфекциях, БА и других заболе-ваниях [20][21][22]. Поэтому NF-κB заслуживает внимания в качестве терапевтической мишени при лечении легочных осложнений ГЭРБ, БА и сочетанной патологии.…”
Section: Discussionunclassified
“…1, строка 12). Чтобы понять причину этих от-личий, надо учитывать, что основным источником IL-2 являются клетки Th1 [22]. В легких и БАЛЖ эти клетки есть, а в среде культивирования макрофагов -нет.…”
Section: терапевтический архив 3 2015unclassified